THE INFLUENCE OF MOTIVATION, TRAINING, AND INTERNAL LEADERSHIP ON EMPLOYEE PERFORMANCE AT PT. ANUGRAH MULTI KREASINDO - Raditantri, Risti; Taufik, Kemal; Hanaffy, Jamal (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
Amid the rapid currents of globalization and technological advancement, the success of an organization greatly depends on the quality of its employees, whose performance can be enhanced through strong motivation, proper training, and inspiring leadership. This study aims to analyze the influence of motivation, training, and leadership on employee performance at PT Anugrah Multi Kreasindo. The research population consisted of 250 employees, with a sample of 100 respondents determined using a probability sampling technique with the simple random sampling method. Data were collected through questionnaires and observations. This study employed a descriptive quantitative approach, with data analyzed using SPSS version 20. The results of the study indicate that motivation, training, and leadership have a positive and significant effect on employee performance. These findings suggest that improvements in motivation, effective training, and strong leadership can enhance the performance of employees at PT Anugrah Multi Kreasindo.